Osteoporosis and Bone Density Studies: Does treatment help decrease mineral loss? - Ehrlich, Lisa (1992)
Osteoporosis is a growing problem in Canada due to our aging population. It is associated with an increased frequency of fractures and disability. As medical therapies become available to help stabilize or prevent bone loss, it will be important to document bone mineral density before treatment and to ascertain the effectiveness of therapy. Studies such as single-photon absorptiometry, dual-photon absorptiometry, and quantitative computed tomography are all available for this purpose.